Effect of occupation on risk of developing MS: an insurance cohort study. Issue 6 (11th June 2013) - Horwitz, Henrik; Ahlgren, Birgitte; Nærum, Elisabeth
Abstract : Objective: The aim of this study was to estimate the occupational risks in relation to multiple sclerosis (MS). The immediate background for this research was our finding that there had been a high number of critical illness insurance claims by patients diagnosed with MS within the agricultural segment of a Danish pension fund. Design: An open insurance cohort. All payouts for the critical illness insurance from 2002 to 2011 were continuously registered. Settings: PensionDanmark; one of Denmark's largest pension funds. Participants: PensionDanmark insures more than 300 000 members of the Danish Confederation of Trade Unions against critical illness. All members are insured, and all policies are identical. The total exposure is 3.3 million person-years. Primary outcome measures: The incidence of MS. Results: During the 10-year period, 389 persons were diagnosed with MS. The crude incidence rate for men was 10.2/100 000; the corresponding figure for women was 16.1/100 000. We found signs of an overall effect of occupation on the risk of developing MS, and the high frequency found within the agricultural segment was attributed to dairy operators, who had an incidence of MS 2.0 times higher than the rest of the study's population (95% CI=1.2 to 3.0). Conclusions: Our results indicate some occupational risk factors in MS, and this should be investigated further.